Cropping Scenario in Water User Associations (WUAs) Managed Groundwater Irrigation System’s Command Area in West Bengal - Mukherjee, Subhajit; Ghosh, Souvik (Indian Journal of Extension Education, 2022)
The groundwater irrigation, catering to more than 60 per cent of total irrigation in India, has significantly contributed to food grains production. Participatory irrigation management programme has been implemented transferring irrigation management to WUAs. Present study was undertaken during 2019 to explore cropping scenario in groundwater irrigation command under jurisdiction of WUAs in Burdwan district of West Bengal covering a random sample of 120 farmers. It is revealed that paddy was the major crop in both kharif and summer season. During rabi season, potato was grown in larger areas followed by mustard. While all 120 farmers had grown paddy as single crop in kharif season, 100 and 82 farmers have cultivated potato and mustard in rabi season and 75 farmers have grown boro rice during summer season. Cultivated land utilization index value was more than 50 per cent. Crop diversity index (CDI) value of 36 per cent showed lack of crop diversification in groundwater irrigation command areas that warrants need of bringing more areas under different crops. Multiple cropping index of 176 per cent showed a higher cropping intensity in groundwater irrigation command. Thus, Extension advisory services need to promote crop diversification in groundwater irrigation command areas through proper crop planning and capacity building of WUAs.
Keywords: Irrigation; Groundwater; Farmers; Participatory irrigation management